2023
DOI: 10.1111/ddg.15022
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐DFS70 antibodies are associated with atopic dermatitis and can cause misdiagnosis of connective tissue disease

Abstract: Background and Objectives: Antinuclear antibodies (ANA) detected by HEp2 cell immunofluorescence staining are a characteristic finding in patients with connective tissue disease (CTD). However, even detection of highly elevated ANA is not conclusive for CTD and can result in misdiagnosis. Anti-DFS70 antibodies are ANA, which may also be highly elevated in people without CTD. Thus, we wanted to evaluate whether they could cause misdiagnosis of CTD. Since anti-DSF70 antibodies have been associated with atopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Among these samples, the CSFs of nine patients with schizophrenia and six controls were positive for DFS70 antibodies. DFS70 is an antinuclear antibody that is associated with atopic dermatitis and asthma [ 34 , 35 ]. Although DFS70 has also been detected in healthy individuals, its pathogenic significance remains unclear [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these samples, the CSFs of nine patients with schizophrenia and six controls were positive for DFS70 antibodies. DFS70 is an antinuclear antibody that is associated with atopic dermatitis and asthma [ 34 , 35 ]. Although DFS70 has also been detected in healthy individuals, its pathogenic significance remains unclear [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Der Nachweis eines erhöhten ANA-Titers alleine hat eine sehr geringe Spezifität für die Diagnose einer Kollagenose, während der Nachweis erhöhter ANA und spezifischer Autoantikörper -wie zum Beispiel Anti-dsDNA-Antikörper -eine frühe Diagnose oder eine Prognose über den Krankheitsverlauf ermöglichen können. [1][2][3] Aus diesen Gründen sind ANA auch in anderen Fachrichtungen als der Rheumatologie zu einem beliebten diagnostischen Werkzeug geworden.…”
Section: Introductionunclassified
“…A previous study reported that the presence of anti-DFS70 could be used as a biomarker to exclude SARDs from healthy individuals with positive ANA [32]. Knowing the serological and clinical profile of anti-DFS70-positive subjects may help to prevent unnecessary cases to specialists and requests for further testing in healthy individuals [32][33][34]. The gold standard for anti-DFS70 testing is the IIF assay.…”
Section: Introductionmentioning
confidence: 99%